2013
DOI: 10.1136/archdischild-2013-303838
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of uptake of free vitamins in England

Abstract: ObjectiveTo identify reasons why eligible families are not accessing free ‘Healthy Start’ vitamin supplementation (providing vitamins A, C and D) in England.DesignQualitative study using in-depth interviews.Setting13 primary care trusts in England.ParticipantsPurposive sample of 15 Healthy Start coordinators, 50 frontline health and children's professionals and 107 parents.ResultsVitamin take-up was low across all research sites, reported as below 10% of eligible beneficiaries for free vitamins. Reasons identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 14 publications
7
42
0
2
Order By: Relevance
“…2 An advice sheet advocating this has been written by the authors of this ALSPAC cohort study, 2 but a higher iodine intake has not previously been suggested in the UK due to lack of evidence of its benefit. 3 The infrastructure may already be there to implement this advice concerning increased intake, with schemes such as Healthy Start providing subsidised nutritious foods supplements. Even though there is low uptake of such schemes at present, 4 with more backing and improved accessibility it may be possible to enhance borderline diets in the most vulnerable.…”
Section: Resultsmentioning
confidence: 99%
“…2 An advice sheet advocating this has been written by the authors of this ALSPAC cohort study, 2 but a higher iodine intake has not previously been suggested in the UK due to lack of evidence of its benefit. 3 The infrastructure may already be there to implement this advice concerning increased intake, with schemes such as Healthy Start providing subsidised nutritious foods supplements. Even though there is low uptake of such schemes at present, 4 with more backing and improved accessibility it may be possible to enhance borderline diets in the most vulnerable.…”
Section: Resultsmentioning
confidence: 99%
“…The operation of the Healthy Start scheme, which provides free vitamins to low-income families, is also very complex,34 leading to low uptake, poor accessibility and lack of motivation to take daily supplements,35 not to mention the lack of parental awareness 36. Apart from the complexity of the guidance, it is mainly the complete lack of accountability and monitoring that is responsible for the failing of the Healthy Start programme to improve the vitamin D status of the at-risk population 34.…”
Section: Factors Contributing To Resurgence Of Rickets In the Ukmentioning
confidence: 99%
“…In the UK, a system of coupons exchangeable for bottles of vitamin D has been instituted by the National Health Service (NHS) and has partially succeeded [6]. Turkey provides vitamin D via prescription [7].…”
Section: Introductionmentioning
confidence: 99%